The effect of supplementation of synbiotic in Thai Native chicken diets on production performance, intestinal histomorphology and carcass quality - Raksasiri, B. V.; Chotnipat, S.; Thongklai, K.; Khotsakdee, J.; Injana, W.; Nopparatmaitee, M. (International Journal of Agricultural Technology, 2021)
This syudy focused on the effect of synbiotic supplementation in Thai native chicken diets, on production efficiency and morphology in the intestines of chickens where Jerusalem artichoke (Helianthus tuberosus L.) and BACTOSAC-P® were used as synbiotic sources, respectively. The results showed that final weight, ADG, and FCR were statistically different. (P<0.05) with values of 2,422.35, 2,497.40, 2,585.70 and 2,599.12, (g); 25.45, 26.25, 27.25, and 27.44, (g/day); 2.98, 2.92, 2.74, and 2.86 respectively. While, the values of villous height, cryptal depth, lactic acid bacteria and NH3 production were not statistically different. Carcass quality studies showed that the total internal organ was significantly reduced. (P<0.05) with values of 11.78 10.32 10.26 and 10.18 (%), respectively. However with, meat quality,it was found that the lightness (L*value) was significantly reduced (P<0.05) with values of 50.51, 48.81, 48.90, and 49.61, respectively and the reflectance of redness (a*) was significantly increased (P<0.05) with values of 1.57, 1.92, 1.96, and 1.81 respectively. Overall, the synbiotic supplementation from Jerusalem artichoke and BACTOSAC-P® can increase growth parameters of Thai native black-tailed chickens, including weight gain, final weight, ADG and FCR. Increased villi height from synbiotic. feed supplementation suggests increased efficiency of nutrient absorption and improved chickens’helalth